Transformations of the Globalized World and Property Rights During the Validity of the Peruvian Civil Code: Twenty Years of Imperialist Plunder and the Potential for Resistance of Jurists - Mattei, Ugo (2005)
The development of property law in Latin American countries such as Peru reflects the profound influence of Western legal cultures. These imported legal concepts have validated structures of domination and economic dependence, thus limiting the development of legal systems that truly respond to local needs. In this context, the uncritical adoption of foreign legal institutions has led Latin American lawyers to lose sight of the history and culture of their countries. On the contrary, it has reinforced a legal practice that serves international interests rather than local needs. Faced with this situation, the author calls on the Peruvian legal system to remember the challenge for Latin America to develop its own institutional organisation and emancipate itself from neo-colonial domination. In this way, Latin America should move towards integration in all legal, political, economic and cultural aspects, promoting a common legal identity that could include the creation of a unified civil code.